Iridoids and anti-inflammatory properties of n-butanol extract of Linaria tingitana Boiss. & Reut. Issue 17 (2nd September 2017) - Hanfer, Mourad; Cheriet, Thamere; Ameddah, Souad; Mancini, Ines; Seghiri, Ramdane; Menad, Ahmed; Benayache, Samir; Benayache, Fadila
Abstract: The analysis of the n -butanol extract of Linaria tingitana (BELT) by HPLC-DAD–ESI/MS allowed the identification of four iridoids structurally confirmed by NMR and ESI–MS/MS extensive experiments data. The subjection of BELT to the anti-inflammatory activity showed that it exhibited a concentration dependent stabilisation of HRBC membrane, inhibition of protein denaturation and nitric oxide scavenging effect in the in vitro process. These results were confirmed in the in vivo experiments which showed that BELT was found to be most pronounced at 200 mg/kg after carrageenan injection which significantly reduced the swelling in both early and late phases of carrageenan-evoked oedema, as well as a significant reduce at the accumulation of infiltrating cells, inhibition of the myeloperoxidase activity and suppressed the lipid peroxidation. These results were supported by the histological analysis which revealed the reduction of oedema and cells infiltration, this might be influenced by the synergistic action of the above isolated compounds. Abstract :